2022
DOI: 10.3389/fcell.2022.839177
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Roles of LINC00665 in Human Cancers

Abstract: Long non-coding RNAs (lncRNAs) are non-coding RNAs that have more than 200 nucleotides and can participate in the regulation of gene expression in various ways. An increasing number of studies have shown that the dysregulated expression of lncRNAs is related to the occurrence and progression of human cancers. LINC00665 is a novel lncRNA, which is abnormally expressed in various human cancers, such as lung cancer, breast cancer, prostate cancer, and glioma. LINC00665 functions in many biological processes of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Furthermore, the up-regulated LINC00665 in osteoarthritis was found in this study. As a concerned lncRNA associated with human disease, LINC00665 was reported to increase dramatically in cell models of cerebral ischemia–reperfusion injury [ 24 ], and it was also enhanced in numerous tumors such as breast cancer and prostate cancer [ 25 ]. Deng et al [ 26 ] found that LINC00665 was elevated in rats with spinal cord injury, and inhibition of its expression was beneficial to cell survival and control inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the up-regulated LINC00665 in osteoarthritis was found in this study. As a concerned lncRNA associated with human disease, LINC00665 was reported to increase dramatically in cell models of cerebral ischemia–reperfusion injury [ 24 ], and it was also enhanced in numerous tumors such as breast cancer and prostate cancer [ 25 ]. Deng et al [ 26 ] found that LINC00665 was elevated in rats with spinal cord injury, and inhibition of its expression was beneficial to cell survival and control inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of CRNDE regulates cancer cell proliferation, migration, invasion, and apoptosis through multiple signaling pathways, such as WNT/β-catenin (Yu et al, 2017), PI3K/AKT (Liu et al, 2017), and mTOR (Wang et al, 2015) signaling pathways. LINC0066 is aberrantly expressed in a variety of human cancers and acts as an oncogene or tumor suppressor gene (Zhu et al, 2022). Silencing LINC00665, which is associated with poor prognosis in gliomas, suppressed the expression of markers of EMT (Lu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA LINC00665 participates in the TGF-β signaling pathway besides five other signaling pathways including the Wnt/β-catenin, NF-κB, PI3K/AKT, and MAPK signaling pathways. Aberrant expression of LINC00665 in BC is associated with poor prognosis and affects cisplatin-paclitaxel treatment [73].…”
Section: Tgf-β/smadmentioning
confidence: 99%